Zoonotic diseases in high-risk populations in the Free State province, South Africa - Van der Westhuizen, Cornelius Gerhardus (University of the Free State, 2021)
Zoonotic diseases are infectious diseases transmitted from vertebrate animals to humans and are accountable for more than 60% of all recognized human diseases and 75% of all new or emerging infectious diseases (EID). In South Africa (SA), endemic zoonoses include Mycobacterium bovis (M. bovis), Brucella sp., and Leptospira sp. The prevalence and burden of other pathogens, such as hantaviruses, are unknown. Therefore, identifying high-risk occupations and other risk factors are important for control and preventative measures to decrease the disease burden of these zoonoses. Thus, this study aimed to investigate the incidence rate of M. bovis and Brucella sp. in cattle and farm workers in two different farming communities (communal and commercial), as well as their associated risk factors. This study aimed to document occupational exposure to Brucella sp., Leptospira sp. and hantaviruses across the Free State province, South Africa. Four commercial farms and a rural cattle farming community within the Moqhaka and Ngwathe municipal regions were selected for the purpose of this study. From these farms, sputum and blood specimens were collected from 13 commercial farm workers and 13 communal farm workers. Sputum samples were screened for M. bovis through Mycobacteria Growth Indicator Tube (MGIT) culture. Blood specimens from these 26 farm workers, in addition to 301 archived sera, were screened for Brucella sp., hantaviruses, and Leptospira sp. antibodies using commercially available enzyme-linked immunosorbent assays (ELISA). From the 26 farm workers, no M. bovis was isolated. Out of the 327 sera screened, 35/327 (10.7%) were Brucella sp. IgG positive, 17/327 (5.2%) Leptospira sp. IgM positive, and 38/327 (11.6%) hantavirus IgG positive. A combined total of 321 cattle were screened for M. bovis through tuberculin skin testing (TST); 71 cattle were from communal farms and 250 from commercial farms. Additionally, blood samples collected from 69 and 1793 cattle within the communal and commercial farms, respectively, were screened for Brucella sp. using a Rose Bengal test (RBT) and complement fixation test (CFT). A total of 8/321 (2.5%) cattle reacted positive to the TST, and two were positive using the interferon-gamma release assay. Initial RBT screening resulted in 52/1859 (2.8%) positive results, further testing using a CFT identified 19/1859 (1%) brucellosis-positive cattle. A higher percentage of brucellosis-positive animals were from communal cattle (6/69; 8.7%) compared to commercial cattle (13/1859; 1.1%). Statistical analysis and probability values were calculated using a chi-squared or Fisher's exact test in the case of sparse data. Analysis identified higher Brucella sp. occupational exposure in veterinarians (p-value = 0.0006) and laboratory workers (p-value = 0.031). Further analysis showed a statistically significant correlation between people who reported illness post-exposure to animal blood/tissue (p-value = 0.029); and older age (p-value = 0.0008) with Brucella sp. seropositivity. Working at the abattoir (p-value = 0.024) was identified as a high-risk occupation for contracting Leptospira sp. In conclusion, the low incidence rate of M. bovis in cattle suggests limited contact with known reservoirs (i.e. buffalo or other wildlife). However, the higher incidence rate of brucellosis in communal cattle highlights the importance of implementing mass herd vaccination campaigns, particularly in communal settings. This report documents the seroprevalence of Leptospira sp., Brucella sp. and hantaviruses in various high-risk occupations in the Free State province and can be used as a basis for the development and establishment of adequate preventive or control measures.
Dissertation (M.Med.Sc. (Medical Microbiology and Virology))--University of the Free State, 2021
Keywords: Zoonotic diseases; Brucellosis; Tuberculosis; Leptospirosis; Hantavirus; Occupation; Risk factors; Seroprevalence; Cattle